Perbandingan Penyembuhan Ulkus Diabetik dengan Menggunakan Minyak Kelapa Murni, Madu, dan Produk Farmasi - Lisa Suarni; Fitarina Fitarina (Politeknik Kesehatan Tanjung Karang, 2019)
The incidence rate of Diabetes in Indonesia is increasing every year. In as much as 8.7% of Diabetes sufferer, they suffer from diabetic ulcer, and 1,5% undergo body amputation. This condition reveals that the problem needs special attention to treatment. Some researches show benefit and effectivity of wound care with honey and virgin coconut oil (VCO) at some nursing clinics. Nurses and patients have a complaint on the high cost of pharmacy product for wound care available in the market. This research aims to compare 3 types of preparation for diabetic ulcer care. Those are VCO, honey, and pharmacy product, which the last is for group control. This research uses experimental quasi method to compare wound healing in 3 groups using 3 types of solution: honey, VCO, and pharmacy product. It involves samples, 11 respondents for VCO group, 10 respondents for the honey group, and 10 respondents for pharmacy product which serves as a control group. Analysis using dependent t-test proves that there is a score difference between wound care before and after treatment using all types of preparation. Analysis using independent t-test show that there is no difference in wound healing between using VCO and using pharmacy product, also, there is a difference among honey, VCO, and pharmacy product. This research recommends VCO preparation, which has benefit nearly equal to pharmacy product to be an alternative in wound care for rural residents with middle and lower-income.